Functional divergence of the NIP III subgroup proteins involved altered selective constraints and positive selection - Zhu Zhujun; Liu Qingpo (BMC Plant Biology, 2010)
Abstract Background Nod26-like intrinsic proteins (NIPs) that belong to the aquaporin superfamily are unique to plants. According to homology modeling and phylogenetic analysis, the NIP subfamily can be further divided into three subgroups with distinct biological functions (NIP I, NIP II, and NIP III). In some grasses, the NIP III subgroup proteins (NIP2s) were demonstrated to be permeable to solutes with larger diameter, such as silicic acid and arsenous acids. However, to date there is no data-mining or direct experimental evidences for the permeability of such larger solutes for dicot NIP2s, although they exhibit similar three-dimensional structures as those in grasses. It is therefore intriguing to investigate the molecular mechanisms that drive the evolution of plant NIP2s. Results The NIP III subgroup is more ancient with a divergence time that predates the monocot-dicot split. The proliferation of NIP2 genes in modern grass species is primarily attributed to whole genome and segmental chromosomal duplication events. The structure of NIP2 genes is relatively conserved, possessing five exons and four introns. All NIP2s possess an ar/R filter consisting of G, S, G, and R, except for the cucumber CsNIP2;2, where a small G in the H2 is substituted with the bulkier C residue. Our maximum likelihood analysis revealed that NIP2s, especially the loop A (LA) region, have undergone strong selective pressure for adaptive evolution. The analysis at the amino acid level provided strong statistical evidences for the functional divergence between monocot and dicot NIP III subgroup proteins. In addition, several SDPs (Specificity Determining Positions) responsible for functional specificity were predicted. Conclusions The present study provides the first evidences of functional divergence between dicot and monocot NIP2s, and suggests that positive selection, as well as a radical shift of evolutionary rate at some critical amino acid sites is the primary driver. These findings will expand our understanding to evolutionary mechanisms driving the functional diversification of monocot and dicot NIP III subgroup proteins.